(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The use of plant-based molluscicides for snail control is gaining interest due to their eco-friendliness, affordability, availability, and ease of application compared to synthetic molluscicides. In this study, we investigated the molluscicidal potential of the aqueous leaf extract of Antigonon leptopus Hook. & Arn. against two snail species, Bellamya bengalensis Lamarck. 1882 and Lamilidens marginalis Lamarck. 1819. The adult snails were exposed to various concentrations of the plant extract for different time intervals in laboratory conditions. Mortality rates were observed, and the median lethal concentration (LC50) was calculated using probit regression analysis. Water quality parameters were recorded using standard screening methods. The 96-hour LC50 and LC84 values against B. bengalensis were determined as 0.46g/L and 3g/L respectively. For L. marginalis, the 120-hour LC50 and LC84 values were found to be 0.7g/L and 1.12g/L respectively. Phytochemical screening tests revealed the presence of saponins, flavonoids, alkaloids, terpenoids, cardiac glycosides, and tannins in the leaf extract create a synergistic effect of test snails. The observed toxic effect of A. leptopus leaf extract on the snails suggests its ability to interfere with their physiological metabolism, ultimately leading to their death and proofs its potentiality as an effective herbal molluscicide and stupefactant for Pisciculture advancement.